Pengaruh Persepsi atas PP No. 23 Tahun 2018, Pemahaman Perpajakan, dan Kepercayaan pada Pemerintah terhadap Kepatuhan Wajib Pajak UMKM - Elysabeth Fransisca Stevanny; Made Aristia Prayudi (Universitas Pendidikan Ganesha, 2021)
This study intended to know the effect of perception of PP No. 23 of 2018, understanding taxation, and trust in the government towards the compliance of MSMEs taxpayers (Case Study on MSMEs Taxpayers Registered at Singaraja KKP). The form of this research is quantitative research. Purposive sampling technique was used with total 376 respondents. Data collection techniques used using a questionnaire. Data investigation used multiple linear regression analysis using SPSS.20.0 software services for Windows. The results showed that perception of PP No. 23 of 2018, understanding taxation, and trust in the government has a positive effect on tax compliance of MSMEs.